(untitled) (Research, Society and Development, 2020)
The use of grumixama and jambolan in the preparation of food products is an interesting alternative, when considering the bioactive compounds present and their sensorial characteristics. In order to propagate the consumption of these fruits, both jams and yogurts of grumixama and jambolan were developed. The analysis of moisture content, fixed mineral residue, proteins, lipids, fibers, pH, acidity, and soluble solids were performed on the products obtained. The sensorial acceptability of the products was verified by hedonic scale tests and purchase intention. The influence of the type of processing was verified by the quantification of the total phenolic compounds, anthocyanins, and antioxidant activity. It has been found that the chemical composition and physical characteristics of the products developed are similar to other jams and yoghurts produced with different fruits. Processing grumixama and jambolan into jam reduced the phenolic content from 664.58 to 613.07 and 590.67 to 563.08 mg GAE/100 g, the anthocyanin content from 1.46 to 0.14 and 4.37 to 2.23 mg/100 g, and the antioxidant activity from 1273.25 to 1522.63 and 1292.53 to 1427.23 g sample/g of DPPH, respectively. However, the amount of these compounds in jams is still significant. The acceptability index was over 70% for all products, and majority of the tasters indicated (66% for the jams of grumixama and jambolan, 70% for the yogurt of jambolan and 55% for the yogurt of grumixama) that they would probably or would certainly buy the products, showing that it was well received. Therefore, the results obtained indicate potential use of these fruits in food products.